Clonal differences between Non-Typhoidal Salmonella (NTS) recovered from children and animals living in close contact in the Gambia. - Michel M Dione; Usman N Ikumapayi; Debasish Saha; Nuredin I Mohammed; Stanny Geerts; Margareta Ieven; Richard A Adegbola; Martin Antonio (Public Library of Science (PLoS), 2011)
BACKGROUND:Non-Typhoidal Salmonella (NTS) is an important cause of invasive bacterial disease and associated with mortality in Africa. However, little is known about the environmental reservoirs and predominant modes of transmission. Our study aimed to study the role of domestic animals in the transmission of NTS to humans in rural area of The Gambia. METHODOLOGY:Human NTS isolates were obtained through an active population-based case-control surveillance study designated to determine the aetiology and epidemiology of enteric infections covering 27,567 Gambian children less than five years of age in the surveillance area. Fourteen children infected with NTS were traced back to their family compounds and anal swabs collected from 210 domestic animals present in their households. Identified NTSs were serotyped and genotyped by multi-locus sequencing typing. PRINCIPAL FINDINGS:NTS was identified from 21/210 animal sources in the households of the 14 infected children. Chickens carried NTS more frequently than sheep and goats; 66.6%, 28.6% and 4.8% respectively. The most common NTS serovars were S. Colindale in humans (21.42%) and S. Poona in animals (14.28%). MLST on the 35 NTS revealed four new alleles and 24 sequence types (ST) of which 18 (75%) STs were novel. There was no overlap in serovars or genotypes of NTS recovered from humans or animal sources in the same household. CONCLUSION:Our results do not support the hypothesis that humans and animals in close contact in the same household carry genotypically similar Salmonella serovars. These findings form an important baseline for future studies of transmission of NTS in humans and animals in Africa.